Interleukin-22 Attenuated Renal Tubular Injury in Aristolochic Acid Nephropathy via Suppressing Activation of NLRP3 Inflammasome - Wang, Shaofei; Fan, Jiajun; Mei, Xiaobin; Luan, Jingyun; Li, Yubin; Zhang, Xuyao; Chen, Wei; Wang, Yichen; Meng, Guangxun; Ju, Dianwen (Frontiers in Immunology, 2019)
Aristolochic acid nephropathy (AAN), as a rapidly progressive interstitial nephropathy due to excessive ingestion of aristolochia herbal medications, has recently raised considerable concerns among clinicians and researchers as its underlying pathogenic mechanisms are largely unclear. In the current study, we identified NLRP3 inflammasome activation as a novel pathological mechanism of AAN. We found that NLRP3 inflammasome was aberrantly activated both in vivo and in vitro after AA exposure. Blockade of IL-1β and NLRP3 inflammasome activation by IL-1Ra significantly attenuated renal tubular injury and function loss in AA-induced nephropathy. Moreover, NLRP3 or Caspase-1 deficiency protected against renal injury in the mouse model of acute AAN, suggesting that the NLRP3 signaling pathway was probably involved in the pathogenesis of AAN. We also found that administration of IL-22 could markedly attenuate renal tubular injury in AAN. Notably, IL-22 intervention significantly alleviated renal fibrosis and dysfunction in AA-induced nephropathy. Furthermore, IL-22 largely inhibited renal activation of NLRP3 inflammasome in AA-induced nephropathy. These results indicated that IL-22 ameliorated renal tubular injury in AAN through suppression of NLRP3 inflammasome activation. In summary, this study identified renal activation of NLRP3 inflammasome as a novel mechanism underlying the pathogenesis of AAN, thus providing a potential therapeutic strategy for AAN based on suppression of NLRP3 inflammasome activation.